Bandungbergerak dan Perjuangan Masyarakat Dago Elos terhadap Hak Atas Tanah: Advokasi dan Pemberdayaan oleh Civil Society - Dhinda Dwi Maharani; Shabina Sundus Addinari; Muradi Muradi (Yayasan Literasi Sains Indonesia, 2025)
The agrarian conflict in Dago Elos reflect the complexity of land ownership of land ownership issues in Indonesia, which are often shaped by colonial legal legacies and power imbalances. This study aims to analyze the role of BandungBergerak as part of civil society in supporting the struggle of Dago Elos residents to defend their land rights. The research employs a descriptive qualitative method, using interviews with key informants and literature studies from academic sources and media publications. The findings reveal that BandungBergerak functions not only as an alternative media outlet providing critical information but also actively engages in advocacy, community empowerment, and civil society networking. These roles are manifested in in-depth reporting, educational programs, trauma healing, and cultural initiatives that strengthen community solidarity. Applying Charles Tilly’s social movement theory, the struggle of Dago Elos residents can be understood as a consistent social movement characterized by campaigns, diverse repertoires of action, and the WUNC (worthiness, unity, numbers, commitment) display. This study underscores the significant contribution of alternative media such as BandungBergerak in reinforcing local democracy through community accompaniment and the expansion of public participation spaces.